Climate change, climate variability and adaptation options - Neufeldt, Henry; Sand, Isabel van de; Dietz, Johannes; Minh HH; Yatich, T.; Lasco, Rodel; Noordwijk, Meine van (World Agroforestry Centre, 2011)
This section introduces some basic concepts surrounding the climate system, climate change and climate variability. We will provide some insights into the challenges of climate modelling and what the inherent uncertainty really means for us, before exploring the way adaptation has so far been discussed and institutionalized.